In situ monitoring of the acetylene decomposition and gas temperature at reaction conditions for the deposition of carbon nanotubes using linear Raman scattering - Reinhold Lopez, Karla; Bräuer, Andreas; Popovska, Nadejda; Leipertz, Alfred (Optics Express, 2010)
To understand the reaction mechanisms taking place by growing carbon nanotubes via the catalytic chemical vapor deposition process, a strategy to monitor in situ the gas phase at reaction conditions was developed applying linear Raman spectroscopy. The simultaneous determination of the gas temperature and composition was possible by a new strategy of the evaluation of the Raman spectra. In agreement to the well-known exothermic decomposition of acetylene, a gas temperature increase was quantified when acetylene was added to the incident flow. Information about exhaust gas recirculation and location of the maximal acetylene conversion was derived from the composition measurements.